ATIM-24. INTERIM RESULTS OF A PHASE II MULTICENTER STUDY OF THE CONDITIONALLY REPLICATIVE ONCOLYTIC ADENOVIRUS DNX-2401 WITH PEMBROLIZUMAB (KEYTRUDA) FOR RECURRENT GLIOBLASTOMA; CAPTIVE STUDY (KEYNOTE-192). (5th November 2018) - Zadeh, Gelareh; Lang, Frederick; Daras, Mariza; Cloughesy, Timothy; Colman, Howard; Ong, Shirley; Ramakrishna, Rohan; Vogelbaum, Michael; Groves, Morris; Nassiri, Farshad; Frederick, L Sue; Gammon, Karen; et al.
Abstract: BACKGROUND: DNX-2401 (tasadenoturev) is a replication-competent, tumor-selective, oncolytic adenovirus. A dose-escalating, Phase II study of a single intratumoral injection of DNX-2401 with pembrolizumab to determine optimal dose, safety and efficacy is ongoing and enrolling up to 48 patients with recurrent glioblastoma. Key inclusion criteria include patients with a single lesion at first or second recurrence for which resection is not possible or planned. METHODS: In a dose-escalation design, a single intratumoral dose of DNX-2401 (5e8vp, 5e9vp, 5e10vp) is administered via cannula, followed 7 days later by 200 mg pembrolizumab Q3wk for up to 24 months or until confirmed progression, intolerable toxicity, or study withdrawal. Tumor response is assessed every 4 weeks for 6 months and every 8 weeks thereafter. RESULTS: As of 01May2018, 23 patients have been treated, with 17 at the optimal dose of 5e10vp DNX-2401. The median age and KPS at entry was 52 years (26–65) and 90 (80–100), respectively. The most frequent related grade 3–4 AEs across cohorts are headache (30%), fatigue (9%), and increased GGT (9%) consistent with disease or immune activation. Transient grade 1–3 lymphopenia has also been observed. Several cases of vasogenic edema have been managed with steroid tapers or low-dose bevacizumab. No patient has died or discontinued due to study treatment. The median treatment duration is 5.1 months for evaluable patients treated with DNX-2401 and pembrolizumab (N=15). Preliminary efficacy includes two partial responses and 100% 9-month survival for the first 7 patients treated. CONCLUSIONS: DNX-2401 followed by pembrolizumab is well tolerated, and data emerging for disease control and survival are encouraging. Updated results will be presented.